Female genital mutilation and obstetric outcome: A cross-sectional comparative study in a tertiary hospital in Abakaliki South East Nigeria - Chidebe C. Anikwe; Brown N. Ejikeme; Nworah J. Obiechina; Bartholomew C. Okorochukwu; Johnson A. Obuna; Fidelis A. Onu; Lenard O. Ajah (Elsevier, 2019)
Background: Female genital mutilation (FGM) is an assault on womanhood. Objective: To compare the obstetric outcome between parturient with genital mutilation with a cohort that has no genital mutilation. Materials and methods: This cross-sectional prospective study was done in the labour ward of Federal Teaching Hospital Abakaliki between 1st January 2013 and 31st December 2013. The obstetrics outcome of 260 consenting healthy parturients with FGM in the 1st stage of labour was compared with 260 cohorts with no FGM and also in labour. Data were obtained with a structured questionnaire and analysed using IBM SPSS Statistic version 20. Simple percentage odd ratio and Chi-square were used for data analysis at a p-value of < 0.05. Results: The mean age and gestational age of the women were 27.9 ± 4.8 years and 38.9 ± 1.5 weeks respectively. Majority of the women, 308 or 77.0%, belonged to social class 4 and 82.0% had Type 2 FGM. More than 90.0% of the women had a vaginal delivery and the 2nd stage of labour lasted more than 2 h in 13.4% of the women (OR = 0.78 95% CI 0.64-0.97). Parturient with FGM had increased odd of perineal tear (OR = 0.76 95% CI 0.63 - 0.91) and episiotomy (OR = 1.69 95% CI 1.17-2.45). The mode of delivery and neonatal Apgar scores were not significantly influenced by the presence of FGM (P > 0.05). Conclusion: The study has shown that FGM in labour increases the odds of developing perineal trauma which may be associated with a host of short- and long-term complications. We recommend continued awareness creation to stop FGM. Keywords: FGM, Episiotomy, Perineal tear, Haemorrhage